Comparison of Intravoxel Incoherent Motion Diffusion-Weighted MR Imaging and Arterial Spin Labeling MR Imaging in Gliomas. (5th April 2015) - Lin, Yuankai; Li, Jianrui; Zhang, Zhiqiang; Xu, Qiang; Zhou, Zhenyu; Zhang, Zhongping; Zhang, Yong; Zhang, Zongjun
Abstract : Gliomas grading is important for treatment plan; we aimed to investigate the application of intravoxel incoherent motion (IVIM) diffusion-weighted imaging (DWI) in gliomas grading, by comparing with the three-dimensional pseudocontinuous arterial spin labeling (3D pCASL). 24 patients (13 high grade gliomas and 11 low grade gliomas) underwent IVIM DWI and 3D pCASL imaging before operation; maps of fast diffusion coefficient (D ∗ ), slow diffusion coefficient (D ), fractional perfusion-related volume (f ), and apparent diffusion coefficient (ADC) as well as cerebral blood flow (CBF) were calculated and then coregistered to generate the corresponding parameter values. We found CBF andD ∗ were higher in the high grade gliomas, whereas ADC, D, andf were lower (allP < 0.05 ). In differentiating the high from low grade gliomas, the maximum areas under the curves (AUC) ofD ∗, CBF, and ADC were 0.857, 0.85, and 0.902, respectively. CBF was negatively correlated withf in tumor (r = - 0.619, P = 0.001 ). ADC was positively correlated withD in both tumor and white matter (r = 0.887, P = 0.000 andr = 0.824, P = 0.000, resp.). There was no correlation between CBF andD ∗ in both tumor and white matter (P > 0.05 ). IVIM DWI showed more efficiency than 3D pCASL but less validity than conventional DWI in differentiating the high from low grade gliomas.